Architecture drawing for toilet of PT5+PT6+UT3(2F) (RFA-543_Rev. B) - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of only PDF version of drawings.